Effects of Dietary Electrolyte Balance and Crude Protein Level on Growth Performance, Carcass Characteristics, and Blood Analytes of Finishing Pigs - J. Soto; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 288 finishing pigs (PIC 327 × 1050, initially 243.5 lb) were used in a 20-d trial to determine if dietary electrolyte balance (dEB) in conjunction with low protein, amino acid fortified diets has any influence on growth performance. Pens of 8 pigs were allotted by BW and randomly assigned to 1 of 4 dietary treatments with 9 replications per treatment. Treatments were arranged in a 2 × 2 factorial with main effects of CP (10 or 13%) and dEB (48 or 107 mEq/kg). At d 20, the pigs were transported to a packing plant for processing and carcass data collection. Pigs fed 13% CP diets had greater (P = 0.001) ADG, heavier (P = 0.037) final body weight, and improved (P<0.001) feed efficiency compared with pigs fed the 10% CP diets. A tendency for a CP × dEB interaction was observed for ADFI because intake numerically decreased when dEB was increased for pigs fed 10% CP, whereas intake increased as dEB was increased for pigs fed 13% CP diets. For carcass performance, pigs fed the diets with 13% CP had increased (P = 0.001) HCW and HCW ADG and improved (P = 0.001) HCW F/G compared with pigs fed the 10% CP diets. In conclusion, reduced performance observed in pigs fed the low crude protein diets with high supplemental crystalline AA was not influenced by dEB ranging from 48 to 107 mEq/kg. Dietary electrolyte balance in the range tested had no effects on growth performance, HCW, yield, or carcass performance during late finishing. Appropriate levels of dietary CP are critical to ensure optimal late finishing performance.
Keywords: crude protein; electrolyte balance; late finishing